Evaluación de dos cepas de Bradyrhizobium spp. en tres diferentes dosis dentro del cultivo de soya (Glycine max), en la zona de La Maná, provincia de Cotopaxi. - Martínez Meza, Alex Javier (2023)
This project was carried out in the El Moral sector, in the El Triunfo parish, in the La Maná canton, with the objective of evaluating two strains of Bradyrhizobium spp. (Bradyrhizobium elkani and Bradyrhizobium japonicum), in the soybean crop (Glycine max), to determine the bacteria and dose that present the best symbiotic response within the crop and its productive cycle. The variables under study were: days and percentage of plant emergence, plant height, days to flowering, number of flowers, insertion distance of the first pod, number of pods, number of nodules, fresh weight of the plant and weight dry weight of the plant, fresh weight of the root and dry weight of the root, weight of 100 seeds and weight of seeds per treatment. A Random Block Design was used, in a 2x3+2 factorial arrangement (two inoculants, three doses, one conventional control and one control), with four repetitions and four experimental units. The results obtained show that the best response in plant height was recorded with T2 at 15 and 30 days with 18.61 and 37.37 cm, at 45 and 60 days higher height averages were obtained with T5, 105.47 and 143.65 cm; the best period of days to flowering was T5, with 39.06 days from sowing; for the number of flowers the significant results were given with T4, with 35.80 flowers; In the variable insertion distance to the first pod, the shortest distance was obtained with T5, with 18.70 cm; the count of nodules with superior results was presented with T5, reaching 28.44 nodules per plant, the weight of the foliage, both in the fresh and dry state, was registered with T5, with 88.70 and 20.37 g. In the same way, for the root weights in the fresh and dry state, the most outstanding results were presented in T5 with 10.20 and 3.08 respectively. The production data show the weight of 100 seeds with representative results for T5 with 15.89 g., while in the total weight per treatment they locate T5 with results of 1.52 kg. The economic analysis shows that T5 obtained higher income with 3648.00 USD, reaching a net benefit of 2276.00 USD, which represents a benefit-cost ratio of 1.66 USD for each monetary unit invested.